Targets of Salvation: Ovumuila Women with Tuberculosis and the Potential of the "Unreached" in Medical Mission - Plett, Rebecca (Anthropologica, 2015)
The colonial history and political economy of Angola through years of conflict have marginalized the Ovumuila, a proportionately small ethnic group living primarily in the southwestern corner of the country. Yet it is precisely this constructed "backwardness" that has, ironically, rendered them targets of the contemporary colonialist enterprise of medicine and evangelical Christian mission. Drawing on ethnographic fieldwork at a rural clinic, this article discusses how Ovumuila women with tuberculosis are characterized as "unreached" and "at risk," thus providing the impetus for an incessant and penetrating agenda of salvation.